A Likelihood-Based Evaluation of the Segmented Markets Friction in Equilibrium Monetary Models - John S. Landon-Lane; Filippo Occhino (Rutgers University, Department of Economics, 2004)
This paper estimates and compares the full participation and the segmented markets monetary frameworks. In both models, the real sector and monetary policy determine exogenously the joint process for the aggregate endowment and the short-term nominal interest rate, while the money growth rate and the inflation rate are determined endogenously. Using linearized versions of the models, we use Bayesian methods to compare the two models over the full dimension of the data. This likelihood-based comparison overwhelmingly favors the segmented markets model over the full participation model. The estimate of the fraction of households participating in financial markets is approximately 13%. The segmented markets model generates more persistent and more realistic impulse response functions to monetary policy shocks. Our results strongly suggest that taking the presence of market segmentation into account is important in understanding the short-run dynamics of the monetary sector.
Keywords: E52; C52; C11; 330; limited participation; segmented markets; Bayesian model comparison; monetary policy shocks; Geldtheorie; Geldpolitik; Marktsegmentierung; Cash-in-Advance-Modell